Modelling Clinical Guidelines and Protocols for the Prevention of Risks Against Patient Safety - SEYFANG, Andreas (2009)
The detection and prevention of Risks Against Patient Safety (RAPS) are ever-increasing issues in health care. One aspect of the many measures taken against RAPS is the comparison of the actual care practice against descriptions of best practice given in clinical guidelines and protocols (CGPs). In order to perform such comparisons automatically, CGPs need to be modelled in a computer-executable form. In addition, the execution of the CGP model must be integrated with the care process at the site of application, and with risk-assessment tools used by the hospital’s risk manager to explore what-if scenarios. In this paper, we describe the modelling and execution of CGPs in Asbru within the EU project Remine, which develops a high-performance platform for the prediction, detection and monitoring of RAPS.